2018
DOI: 10.21608/ejhc.2018.13923
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Nurses' Performance Regarding Care for Neonates with Necrotizing Enterocolitis at Intensive Care Units

Abstract: Background: Necrotizing enterocolitis is an acquired condition. It is the most common gastrointestinal emergency in the neonatal period and manifested by ischemic necrosis of the intestinal mucosa. Aim of the study was to assess nurses' knowledge and performance regarding care of neonate with necrotizing enterocolitis at neonatal intensive care units. Design: A descriptive research design was utilized in this study. Settings: the study was conducted at neonatal intensive care units of Benha Specialized Pediatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…From the researcher's point of view, this could explained on the basis of associating the good level of nurses' knowledge with the competent level of performance provided for the neonates resulting in improving nurses' compliance regarding care of neonates during convulsion. These findings are in an accordance with the study of Zaki et al, (2018) entitled ʺAssessment of Nurses 'Performance Regarding Care of High Risk Neonates at Intensive Care Unitsʺ Who found that there appositive correlation between nurses 'total knowledge and their total performance. This result also agreed with Hegazy, (2016) who studied nurses' knowledge versus their performance in caring for neonates having convulsion and found that, there was statistically significant difference between total knowledge and total practice of the studied nurses.…”
Section: Part I: Characteristics Of the Studied Nurses And Neonatessupporting
confidence: 91%
“…From the researcher's point of view, this could explained on the basis of associating the good level of nurses' knowledge with the competent level of performance provided for the neonates resulting in improving nurses' compliance regarding care of neonates during convulsion. These findings are in an accordance with the study of Zaki et al, (2018) entitled ʺAssessment of Nurses 'Performance Regarding Care of High Risk Neonates at Intensive Care Unitsʺ Who found that there appositive correlation between nurses 'total knowledge and their total performance. This result also agreed with Hegazy, (2016) who studied nurses' knowledge versus their performance in caring for neonates having convulsion and found that, there was statistically significant difference between total knowledge and total practice of the studied nurses.…”
Section: Part I: Characteristics Of the Studied Nurses And Neonatessupporting
confidence: 91%